PENGADAAN POSTER EDUKASI COVID-19 DAN PELATIHAN PEMBUATAN DISINFEKTAN DI PONDOK PESANTREN AL-FATTAH SIMAN LAMONGAN - Zuhriyyah Hidayati; Laili Nur Syafitri (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
One of the areas affected by the spread of Covid-19 is education, including Islamic boarding schools. After undergoing distance learning in the early days of the emergence and spread of Covid-19, several Islamic boarding schools enforced the reopening of learning in pesantren by implementing strict health protocols. One of them is Pondok Pesantren All-Fattah Siman Lamongan. Unfortunately, not all students understand and understand the health protocol well. Therefore, our team from STIT Al-Fattah, consisting of one lecturer and one student, conducted community service at the Al-Fattah Islamic Boarding School with the agenda of procuring Covid-19 educational posters and training in making disinfectants with the aim of making students and pesantren administrators understand health protocols. which must be implemented during Covid-19. The target of this implementation is all female students of the Al-Fattah Siman Lamongan Islamic Boarding School. As a result of the implementation of this activity, the students felt that they had a better understanding of basic health protocols in dealing with Covid-19.